(untitled) (Conferencea, 2022)
This article is devoted to the study of improving the organizational and economic mechanism of management of food industry enterprises. A brief description of the socio-economic environment of food industry enterprises and its necessary parameters were determined. Some specific features of management of activities in food industry enterprises were considered. The structure of the control mechanism and the characteristics of its components were proposed.